Inclusive Education in Madrasah: Addressing the Needs of Students with Disabilities in Religious - Saona (Sekolah Tinggi Agama Islam Kuningan (STAIKuningan), 2025)
Inclusive education is a major challenge for madrasas that aim to provide equal educational opportunities for students with disabilities. This research highlights the readiness of madrasas in meeting the needs of students with special needs through an assessment of infrastructure, curriculum adaptation, and community attitudes. Using a qualitative case study approach, data was collected through interviews, observations, and documentation. The results show that although most of the community supports inclusive education in madrasas, there are still challenges related to limited infrastructure and teacher training in implementing inclusive learning methods. This study recommends more flexible curriculum updates and increased training for teachers to strengthen the implementation of inclusion in the context of religious education. Thus, madrasas are expected to play a role in supporting wider access to education for students with disabilities, in line with the goal of global inclusive education.